Literature Review on BRI Client’s Coffee Export and Competitive Advantage Through Sustainability - Veronica, Natalia; Ramanda, Diar K.; Perdhana, Mirwan Surya (LifeSciFi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the coffee sector, particularly those supported by BRI Bank, hold significant potential to contribute to national coffee exports. Various structural and operational challenges are still encountered, such as limited access to financing, low levels of technology adoption, and difficulties in meeting international market standards. This study aims to develop an empowerment model that enables MSMEs to build long-term competitive advantage through sustainable business practices. Employing a literature review approach, this study synthesizes previous empirical findings to analyze the role of BRI’s empowerment initiatives such as training, mentoring, and financing in enhancing MSME performance. The findings reveal that sustainability-oriented empowerment focusing on market-driven training, digitalization of export processes, and inclusive financing access significantly enhances the competitiveness of MSMEs. The main contribution of this study is the formulation of an integrated empowerment model based on the Resource-Based View (RBV), emphasizing the development of valuable, rare, and inimitable resources as a foundation for sustainable competitive advantage.